A gamma-ray spectrometry approach to field separation of illuviation-type WRB reference soil groups in northern Thailand - Ulrich Schuler (2018)
According to the World Reference Base for Soil Resources (IUSS Working Group WRB, 2006), the differentiation of Acrisols and Alisols is based on the cation-exchange capacity of clay, which cannot be directly determined in the field, but needs expensive and time-consuming soil-chemical analyses. This is an unsatisfactory situation for pedologists, who urgently require a rapid field method to distinguish illuviation-type reference soil groups (Alisols, Acrisols, Luvisols, Lixisols). In this study, we tested the ability of gamma-ray spectrometry to separate major WRB reference soil groups in the field. The underlying hypothesis is that Alisols and Acrisols are distinguished by their clay mineral composition, which should be reflected by geochemistry and consequently gamma-ray radiation (i.e., K-containing illite vs. K-free kaolinite). Highly significant differences in their gamma-ray spectrum for K, Th, and U were found for limestone and its soils. Especially the K and Th signatures allowed a clear separation of Acrisols and Alisols. In general, the surface radiation was sufficient to separate these soils. Best results were revealed considering parent rock and the whole soil profile. This means by using a portable radiometer and a pH meter, all illuviation-type reference soil groups could be distinguished in this case. If applicable at other sites, this approach could enormously reduce expenditures for soil-chemical analysis needed to assist soil classification.© 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.